PENGGUNAAN MEDIA CELEMEK PINTAR DALAM MENINGKATKAN KEMAMPUAN MENGENAL HURUF HIJAIYAH ANAK USIA 3-4 TAHUN DI KELOMPOK BERMAIN AISYIYAH TENGGARONG TAHUN AJARAN 2018/2019 - Sri - Syahadah; Hanita - Hanita (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2019)
PAUD is an act of providing stimulation as a stimulation to children aged 0-6 years, to achieve maximum growth and development. This was done both and so that the child will be ready to enter the next level of education. To achieve growth and development, it is necessary to develop aspects of cognitive abilities, language, motor skills, arts, social, emotional, religious values, through fun activities. Religious values are developed through Imtaq, hoping children will recognize, know, understand and say Hijaiyah as a developing ability for children to recite as a benchmark for achieving child development. The purpose of this study was to determine the use of Smart Apron Media in improving the ability to recognize letters Hijaiyah Children Age 3-4 Years in the Play Group Aisyiyah Tenggarong, 2019. This research was PTK (Classroom Action Research). This research was carried out with two cycles in which each cycle consisted of 4 (four) stages that had to be passed planning, implementation, observation, and reflection. The subjects of this study were 10 children comprising 4 boys and 6 girls. While the object of this research is the use of smart apron media in improving the ability to recognize Hijaiyah letters. Data collection techniques used are observation and documentation. Based on the results of research in the first cycle, for meetings 1 and 2 have seen an increase of 45% and at the second meeting reached 70%. in the second cycle the first meeting achieved an increase with 72 percent and in the second meeting reached 85%. The results be concluded that by using smart apron media the ability to recognize letters of Hijaiyah as a whole has experienced a good increase in every aspect of its assessment.